The Long-Term Effects of Combined Training and 1-Year Follow-Up in Breast Cancer Survivors - de Paulo, Thais R.S.; Rossi, Fabricio Eduardo; Rossi, Priscila Almeira Queiroz; Neves, Lucas Melo; Freitas, Ismael Forte (International Journal of Sports Medicine, 2025)
The use of aromatase inhibitor (AI) therapy in breast cancer survivors (BCS) has been linked to significant and negative changes in body composition and quality of life. However, the long-term effects (9 months) of combined training (CT=resistance plus aerobic training) following the interruption of CT intervention remain unclear in these variables. Thus, the present study aimed to investigate changes in body composition, bone mineral density, and quality of life during a 1-year follow-up period after 9 months of CT in BCS. Participants were randomized into two groups: CT (n=18) for 9 months, or control group (n=18), with 27 participants (CT=16; control=11) reassessed after the 1-year follow-up. There were significant group×time interactions postintervention, with lower fat mass and fat mass percentage in the CT group. However, after the follow-up period, these values returned to baseline. The CT group shows improvements in quality of life, with higher scores in physical functioning, physical health, social functioning, bodily pain, and vitality compared to the control group. These benefits were maintained after the 1-year follow-up period only in the CT group. This study reinforces the crucial role of consistently maintaining an exercise training program for BCS undergoing AI therapy.
Keywords: exercise; breast cancer; menopause; hormone therapy; physical activity